Structural characteristics and interspecific relationship changes during the succession process of the Fagaceae community in a subtropical forest - Ying, Yuxin; Wu, Zhibin; Yan, Yao; Zhou, Xianzhen; Gao, Wei (Frontiers in Plant Science, 2025)
Interspecific relationships can reflect the relevance of species in particular spatial distribution, and the degree of community adaptation under successional stages. In the past, numerous studies on subtropical forest communities primarily focused on the relationship between a specific dominant tree species or a single succession stage, lacking an understanding of interspecific relationships across different succession stages. Given this gap, this study used the method of space instead of time to study the community structure composition and interspecific relationship of trees with DBH > 1 cm in the subtropical 30-70 a Fagaceae community. The results showed that there was no significant difference in the important values of each tree species during the 30 a and 40 a of community succession. As succession advanced, the importance values of neutral and shade-tolerant species progressively escalated. The stand density reached its nadir during the mid-successional stage (50 years), concurrently achieving peak volume. Throughout succession, the diameter at breast height (DBH) distribution of sun-tolerant species conformed to an inverted J-shape, while shade-tolerant species shifted from an inverted J-shaped to a bell-shaped distribution. Positive interspecific correlations gradually intensified after 50 years, at which point both the biodiversity index and stand density reached their lowest levels, subsequently increasing as succession progressed. At the 70-year mark, a overwhelming majority (93.3%) of species pairs demonstrated no significant correlation, indicative of a more relaxed interspecific relationship. These studies show that in the early stage of community development, the community structure has not yet been finalized. With the advancement of community succession, the competition among species changes from strong to weak. In the later stage of succession, the interspecific relationship is relatively loose, and the phenomenon of seedling renewal and filling occurs in the forest, and a certain dynamic balance is maintained among various species. These results deepen the understanding of species interactions and spatial-temporal changes of community structure in different succession stages of Fagaceae communities in subtropical regions, and provide a theoretical basis for forest managers and vegetation ecological restoration in subtropical regions.